Tournaments in mutual fund families - Alexander Kempf; Stefan Ruenzi (University of Cologne, Centre for Financial Research (CFR), 2004)
In this paper we examine intra-firm competition in the U.S. mutual fund industry. Our empirical study shows that fund managers within mutual fund families compete against each other. They adjust the risk they take dependent on the relative position within their fund family. The direction of the adjustment crucially hinges on the competitive situation within a family. Funds from small families behave in the opposite way than funds from large families. The results are very robust. They hold for different time periods and for different subgroups of funds.
Keywords: 330